Providing nutritional care to cancer patients during the COVID-19 pandemic: an Italian perspective - Lobascio, Federica (Support Care Cancer, 2020)
The COVID-19 outbreak has drastically changed practices inside hospitals, which include oncology routines. In oncology, malnutrition was and certainly still is a frequent problem associated with an increase in treatment-related toxicity, a reduced response to cancer treatment, an impaired quality of life, and a worse overall prognosis. Even in this situation of healthcare crisis, nutritional support in cancer care is an essential element. During the current COVID-19 pandemic, there is a concrete high risk to see a dramatic worsening of cancer patients’ nutritional status, who are left without adequate clinical and nutritional support. The consequences are already reasonably foreseeable and will have a severe negative impact after the emergency. Therefore, we believe that it is essential to try to continue, as far as possible, the activity of clinical nutrition in oncology, by revolutionizing the setting and the approach to patients. For this purpose, the Clinical Nutrition and Dietetics Unit and the Medical Oncology Unit of our hospital, one of the largest community hospital in Lombardy that has been involved in the COVID-19 outbreak management since its inception, have reorganized the clinical routine activity in strict collaboration since the very beginning of the emergency, to better face up to the challenge, while preserving cancer patients’ needs.